Perceptions of Art Therapy in Adolescent Clients Treated Within the School System - Harpazi, Shir; Regev, Dafna; Snir, Sharon; Raubach-Kaspy, Racheli (Frontiers in Psychology, 2020)
Research in School Based Art Therapy has been widely discussed in recent years, and the number of studies that examine staff perceptions and the special characteristics of art therapy within the education system has risen considerably. The current study explored the critical issue of adolescent clients’ perceptions of art therapy in school, from their point of view as clients. The methodology and data analysis were conducted according to the principles of Consensual Qualitative Research (CQR). The sample was composed of 12 adolescent clients, aged 14-18 (M=16), who took part in in-depth semi-structured interviews. The findings were organized into five domains that emerged from the interviews: referrals and initial engagement with therapy, the setting within school, the nature of art therapy at school, the relationship with the art therapist, and the impact of art therapy on these clients. The analysis revealed that although some participants initially agreed to art therapy because it got them out of class and let them have fun instead, they realized after a period of time of art therapy that they were engaged in a personal and emotional process focusing on them which allowed them to express their feelings without fear of judgment. Participants at times used the word “mother” to describe their relationship with the art therapist, and stated that the presence of the art therapist at school made them feel safer and helped them deal with day to day problems. School-based art therapy was seen as having specific advantages according to the participants. Having a therapeutic hour during a stressful school day was considered to give these students an opportunity to relax, and the art therapy room was perceived as a shelter. In addition, when the therapist was perceived as a supportive figure, the whole school experience tended to be perceived as supportive or enabling greater acceptance.